Potensi Biokontrol Trichoderma (T14 dan T7834) Sebagai Antipatogen Phytopthora sp. dan Colletotrichum sp. Secara In Vitro - Pramesti, Nouriza Agfa; Sumardi, Sumardi; Farisi, Salman; Irawan, Bambang (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Anthracnose and crown rot caused by Colletotrichum sp and Phytopthora sp fungi are one of the main problems in guava and pineapple cultivation. This research aims to determine the growth of Trichoderma isolates (T14 and T7834), the potential of the isolates as biocontrol agents and the activity of lipase and chitinase enzymes. Research data was analyzed descriptively qualitatively. This study concluded that the growth graph of Trichoderma isolates began with an increase in mycelium dry weight on day 3, on day 12 the dry weight of mycelium increased rapidly, on day 21 the dry weight of mycelium was constant, on day 30 the dry weight of mycelium decreased. The results of the Trichoderma compatibility test were able to inhibit the growth of the fungus Phtyopthora sp. and Colletotrichum sp. so it is effective as a biocontrol agent to control the pathogenic fungus Phytoptora sp. and Colletotrichum sp. in vitro. However, Trichoderma T7834 is unable to inhibit the growth of the Colletotrichum fungus, so it is less effective as a biocontrol agent. The results of the enzyme activity test showed that Trichoderma was only able to produce the lipase enzyme, so the two isolates had the potential to be candidates for biocontrol fungi.